The Relationship Between Glucose Tolerance and Pancreatic: Exocrine or Endocrine Function in Chronic Liver Diseases - SAKAKIBARA, Akira; KATO, Katsumoto; HAYAKAWA, Tetsuo; NAKAMURA, Masao; OKUMURA, Nobuyoshi; TAKEI, Takeshi; SUZUKI, Toshiyuki; TAKEICHI, Masayuki; YAMAZAKI, Yoshihiro (Kanzo, 1978)
Pancreozymin-secretin test and glucose tolerance test were performed in 101 patients with chronic liver diseases. Responses of serum insulin and plasma glucagon to glucose or arginine load were also studied in some cases of them. Mild pancreatic exocrine insufficiency was found in 35% of all subjects, but these cases showed no different glucose tolerance and pancreatic endocrine function from those which healthy controls did. Moderate to severe insufficiency was observed in 11% of non-cirrhotic cases and in 6% of cirrhotic cases, and most of them were alcoholics. In these cases glucose intolerance or pancreatic endocrine insufficiency were more often found than mild exocrine insufficient cases. These results suggest that pancreatic disorder dose not influence on glucose tolerance in all cases with chronic liver diseases, but in non-cirrhotic alcoholics it has important roles. So, in such cases pancreatic exocrine and endocrine function must be studied to determine whether concomitant pancreatic disorder results in glucose intolerance.